Observational Evidence for a Correlation between the Magnetic Field of Jets and Star Formation Rate in Host Galaxies - Yongyun Chen; Qiusheng Gu; Junhui Fan; Xiaotong Guo; Xiaoling Yu; Nan Ding; Dingrong Xiong (The Astrophysical Journal)
Accretion supermassive black holes in the center of active galaxies usually produce “jet”-collimated bipolar outflows of relativistic particles. Magnetic fields near the black hole event horizon may play a crucial role in the formation of jets/outflows. Both theory and observation indicate that jets/outflows driven by centrally active supermassive black holes have a feedback effect on the overall properties of the host galaxies. Therefore, the magnetic field is a key ingredient for the formation and evolution of galaxies. Here, we report a clear correlation between the magnetic field of jets and star formation rate for a large sample of 96 galaxies hosting supermassive black holes, which suggests that the star formation of active galactic nuclei host galaxies may be powered by the jets.